Implementation of Zakat Management According to Law No. 23 of 2011 and MUI Fatwa at BAZNAS Kab. Purwakarta - Kiki Zakiah Nuraisyah; Abdul Wahab Abd Muhaimin; Hidayat, Hidayat (al-Afkar, Journal For Islamic Studies, 2025)
This research has the main aim of carrying out a comprehensive analysis of zakat management at the Purwakarta Regency National Zakat Amil Agency (BAZNAS). The main focus of analysis includes vital aspects in BAZNAS operations, namely the collection and distribution of zakat, as well as including tracing the special programs implemented and the strategies used by BAZNAS in carrying out its activities. This research focuses on qualitative approaches, with the exception of statistical analysis procedures or quantitative methods. The methodology used includes centralized interviews and document studies. The approach adopted in this study is a normative juridical approach, which means that the research is carried out through the analysis of library materials and secondary data only. Researchers analyzed various literary sources such as statutory regulations, scientific journals, and legal literature related to zakat. Thus, this research presents a comprehensive insight into zakat management at the Purwakarta Regency National Zakat Amil Agency (BAZNAS) from a legal perspective. The research results show: First, the zakat collection carried out by BAZNAS Purwakarta Regency is in accordance with the provisions of Law no. 23 of 2011 and the MUI fatwa, it's just that in the collection process BAZNAS Purwakarta Regency did not have a sufficient team, and did not have valid data regarding groups who were required to pay zakat, BAZNAS Purwakarta Regency was very dependent on ASN professional zakat. In fact, the distribution of zakat carried out by BAZNAS Purwakarta Regency is uneven, BAZNAS Purwakarta Regency does not distribute zakat to prostitutes who embrace Islam as riqāb, even though according to data from the Purwakarta Resik Foundation, the number of prostitutes in Purwakarta Regency reaches more than 600 people, if following existing regulations, BAZNAS RI and MUI allow the use of zakat funds to advocate for Muslim women who are entangled in prostitution.